Functionality of the Interleukin 8 haplotypes in lymphocytes and macrophages in response to gram-negative periodontopathogens - Pigossi, Suzane C. [UNESP]; Anovazzi, Giovana [UNESP]; Finoti, Livia S. [UNESP]; de Medeiros, Marcell C. [UNESP]; Mayer, Marcia P.A.; Rossa Junior, Carlos [UNESP]; Scarel-Caminaga, Raquel M. [UNESP] (Elsevier, 2019)
Individuals carrying the ATC/TTC haplotype (Hap-1) in the interleukin 8 (IL8) gene were reported as more susceptible to chronic periodontitis (CP), an infectious disease associated with Gram-negative bacteria, in comparison to patients with the ATT/TTC haplotype (Hap-2). This study investigated the functionality of the IL8 haplotypes in lymphocytes and monocytes of individuals carrying the Hap-1 or Hap-2 IL8 haplotypes in the response to CP-associated Gram-negative bacteria (periodontopathogens). Peripheral blood was collected from 6 subjects carrying each haplotype, and their immune cells were challenged with periodontopathogens or phorbol 12-myristate 13-acetate (PMA) plus Ionomycin. Depending on the immune cell type (lymphocytes or monocyte-derived macrophages) the assessed outcomes were: phenotypical polarization, gene expression, phagocytic activity, chemotaxis and production of reactive oxygen species (ROS). Subjects carrying the Hap-1 haplotype showed increased expression of IL8 and TNFA and significantly skewing towards pro-inflammatory Th1/M1/Th17 phenotypes. There was increased percentage of ROS-producing monocyte-derived macrophages from individuals carrying the Hap-1 haplotype. Cells from individuals presenting the Hap-2 haplotype had an overall attenuated response to periodontopathogens, with a significant shift towards the Treg phenotype. In conclusion, the IL8 haplotypes showed to be functional both in monocyte-derived macrophages and lymphocytes. The Hap-1 haplotype previously associated with increased susceptibility to CP demonstrated greater skewing to pro-inflammatory Th1/M1/Th17 phenotypes and production of ROS.
Keywords: Chemokines; Cytokines; Inflammation; Macrophage; Th1/Th2 cells